Long-term culture of chicken tracheal organoids for the purpose of avian influenza virus research - Anja C. M. de Bruin; Mart M. Lamers; Bart L. Haagmans; Lonneke M. Leijten; Ron A. M. Fouchier; Mathilde Richard (Virology Journal)
Abstract There is an increasing need for reproducible long-term in vitro primary cell culture systems that are representative of the avian respiratory tract to study pathogens like highly pathogenic avian influenza viruses (HPAIVs), which threaten poultry, wildlife, and human health. Self-renewing organoid cultures allow for long-term culture, due to the presence of tissue-resident stem cells, and can approximate the in vivo cellular diversity and organization of tissues. Efforts to establish avian organoid cultures have been limited to the intestinal tract. Here, we describe the isolation and long-term culture of chicken tracheal organoids (CTOs). The CTO cultures were passaged for three to four months and cryopreserved at different stages. Mucociliary differentiation of CTOs was promoted by culture at air–liquid-interface, after which the pseudostratified epithelial cell layer of the avian trachea was recapitulated, including ciliated, goblet, and basal cells. Inoculation of CTO-derived 2D cultures with low pathogenic avian influenza viruses (LPAIVs) and HPAIVs showed that the appropriate receptors, as confirmed by virus histochemistry, and proteases to sustain multi-cycle replication of LPAIVs were expressed and that HPAIVs preferentially disseminated to the endothelium of epithelial/endothelial co-culture systems. Taken together, CTOs represent a useful tool for research on the avian respiratory tract, and their application will generate new insights into host–pathogen interactions, including HPAIV tropism.